2000
DOI: 10.1021/ac991358k
|View full text |Cite
|
Sign up to set email alerts
|

Forbidden Light Detection from Single Molecules

Abstract: We present a new concept for ultrasensitive detection of surface-generated fluorescence which is made possible by a new optical module. The detection method leads to an enhancement in fluorescence collection efficiency to more than 65% of the total of emitted light, whereas high-aperture microscope objectives are able to collect 44% at best. Moreover, by employing this new optical module, the detection volume can be restricted to approximately 10(-17) L. This allows for an exceptional discrimination of bulk-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 24 publications
(23 reference statements)
1
77
0
Order By: Relevance
“…In the future development of biosensors, nanotechnology, including nanomachining techniques [395,396,397,398], will provide bio-microelectromechanical systems (Bio-MEMSs) [399] or nanobiosensing devices (including nanoelectromechanical systems, NEMSs) as new total analytical systems with pumps, valves, reactors, separators, detectors, thermostats, and memories, etc., on chips or arrays. In parallel with such device development, ultrasensitive devices for single-molecule detection will be fabricated on the basis of current studies [30,127,155,168,391,400].…”
Section: Resultsmentioning
confidence: 99%
“…In the future development of biosensors, nanotechnology, including nanomachining techniques [395,396,397,398], will provide bio-microelectromechanical systems (Bio-MEMSs) [399] or nanobiosensing devices (including nanoelectromechanical systems, NEMSs) as new total analytical systems with pumps, valves, reactors, separators, detectors, thermostats, and memories, etc., on chips or arrays. In parallel with such device development, ultrasensitive devices for single-molecule detection will be fabricated on the basis of current studies [30,127,155,168,391,400].…”
Section: Resultsmentioning
confidence: 99%
“…The optical set-up is inverse to that of TIRF with an excitation beam illuminating the sample perpendicularly and a collection of fluorescence light emitted into the supercritical angle of the substrate using a parabolic mirror objective. The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 99%
“…This however led to an increased photobleaching rate of the fluorophores, which is a welcome effect for our approach. The amplitude of the intensity decay obtained after extensive photobleaching of the surface-bound fluorophores serves as a precise measure for the amount of fluorescent analyte present at a surface [21,26]. The resulting background corrected decay amplitude plotted against the IL-2 concentration is shown in Figure 7B.…”
Section: Figurementioning
confidence: 99%